2018
DOI: 10.12968/ajmw.2018.12.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asphyxia and readiness for neonatal resuscitation in Kenya

Abstract: Background: Birth asphyxia accounts for one-third of neonatal mortality worldwide. Aims: To determine the prevalence of birth asphyxia and associated risk factors at one Kenyan hospital; and to describe caregivers' readiness for and attitudes towards neonatal resuscitation of asphyxiated neonates. Methods: A total of 237 babies and 28 health workers were consecutively enrolled as part of a longitudinal cross-sectional study. Prevalence of asphyxia, and caregivers' practices and attitudes were measured through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
4
9
0
Order By: Relevance
“…Inappropriate positioning of the baby's airway, turning baby upside down, and hyperextending the jaw were observed in a considerable number of newborns. These harmful practices have also been reported in previous studies conducted in the country [ 24 , 25 , 35 ]. This indicates that despite all of the HCPs at least having some form of NR training, there is need for further emphasis on practical NR training to help eradicate some of these potentially harmful practices during NR.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Inappropriate positioning of the baby's airway, turning baby upside down, and hyperextending the jaw were observed in a considerable number of newborns. These harmful practices have also been reported in previous studies conducted in the country [ 24 , 25 , 35 ]. This indicates that despite all of the HCPs at least having some form of NR training, there is need for further emphasis on practical NR training to help eradicate some of these potentially harmful practices during NR.…”
Section: Discussionsupporting
confidence: 83%
“…This finding showed that the hospital is well prepared and ready for NR services although HCPs still miss out on key aspects of resuscitation care: removing the wet towel after drying the newborn, suctioning meconium before stimulation/drying the newborn, and initiation BMV within the Golden minute. This points to the need for proper training of HCPs having the equipment for improved NR performance as recommended by other studies in the country [ 25 , 35 ].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In many cases, neonatal resuscitation is a primary requirement for life, especially for neonates with birth asphyxia [1][2][3]. Neonatal resuscitation is particularly important as the first few days following birth are deemed the most vulnerable [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, neonatal resuscitation is a primary requirement for life, especially for neonates with birth asphyxia (Gichogo, Murila, Matiang'i, Ndege, & Bosire, 2018;Pejovic et al, 2018;Wall et al, 2009). Neonatal resuscitation is particularly important as the first few days following birth are deemed the most vulnerable (Babaei & Dehghan, 2018;Owusu, Lim, Makaje, Wobil, & SameAe, 2018;UNICEF, 2015).…”
mentioning
confidence: 99%